Intergenerational mobility of status with multiple dimensions in Germany and the United Kingdom - Michele Bavaro (University of Essex, Institute for Social and Economic Research (ISER), 2018)
This paper proposes a method to estimate intergenerational mobility that takes into account the multidimensionality of the phenomenon. The first premise is that status is unobserved; hence, it must be analysed through latent variable and factor analysis models. The second premise is that the transmission of economic status is a multidimensional phenomenon. The dimensions selected for the status measurement are the resources detained, the occupation performed and the level of education. The results demonstrate that the adoption of a multidimensional approach to the mobility phenomenon severely reduces the estimates of mobility with respect to the unidimensional approach. The empirical application is based on the German SOEP data and the British BHPS-UKHLS.
Keywords: 330